Optimal energy portfolio method for regulable hydropower plants under the spot market - Lu, Guanpeng; Yang, Ping; Li, Zhuangzhuang; Yang, Yi; Tang, Yufeng (Frontiers in Energy Research, 2023)
The energy allocation method for regulable hydropower plants under the spot market significantly impacts their income. The available studies generally draw on the Conditional Value-at-Risk (CVaR) approach, which typically assumes a fixed risk aversion coefficient for generators. This assumption is based on the assumption that the total energy the power plant can allocate is constant during the decision period. However, the amount of energy that the regulable hydropower plant can generate will be affected by inflow and water level during the decision period, and the assumption of the fixed risk aversion coefficient is only partially consistent with the actual decision behavior of the hydropower plant. In this regard, the time-varying relative risk aversion (TVRRA) based method is proposed for the energy allocation of regulable hydropower plants. That method takes the change value of the hydropower plant's energy generation as the basis for adjusting the time-varying relative risk aversion coefficient to make the energy allocation results more consistent with the actual decision-making needs of the hydropower plant. Based on the time-varying relative risk aversion coefficient of regulable hydropower plants, a two-layer optimal method is proposed to obtain the income-maximizing energy portfolio by the inner point method. The dynamic risk preference of hydropower plants for each period is accurately described by the time-varying relative risk aversion coefficient in the inner layer, based on which the optimal energy portfolio of income and risk is solved. The results and comparison show that the proposed method increases the income of the energy portfolio by 31%, and water disposal of regulated hydropower plants is reduced by 2%.